Contribution to the Development of General Model of Management and Strategic Decision-Making ... - Kasum, Josip; Gržetić, Zvonko; Marušić, Eli (Promet - Traffic&Transportation, 2007)
It is assumed that in strategic decision-making in managingnautical tourism p01ts (NTP) various decisions are made onthe basis of desc1iptions, calculations, statistic, economic andother indicators, and also of inadequate number of precise indicators(Branch, A. E., 1998). Therefore, strategic decision-making is slightly uncertain, which, it is assumed, may bemodified. This article explores the new measuring elements.They are developed on the sample of 47 NTPs in the archipelagicsea of the Republic of Croatia. It is assumed that by applyingthe new measuring elements it will consequently result inlowering the unreliability of strategic managing, which willeventually increase the profit of NTP.